Impact of Adjustable External Horizontal Shading Slats on Indoor Visual Comfort in Tropical Climate - Ingabo, Simeon Nyambaka; Chaiwiwatworakul, Pipat; Mettanant, Vichuda (Naresuan University Journal: Science and Technology (NUJST), 2020)
The main function of windows is to provide natural light and a view of the outdoor surroundings. Excessive direct sunlight penetrating into interior spaces through the windows poses glare and contrast problems in addition to excessive beam solar radiation which leads to high cooling loads. Shading slats are installed to block beam radiation and enhance the general visual environment for building occupants.  Despite their proven energy saving potential, building designers tend to shun these shading devices for reasons such as maintenance costs, aesthetics, glare possibility and their interference of occupants’ view of the outdoor surroundings. In this paper the impact of adjustable external horizontal shading slats on occupants’ visual comfort and view was investigated. Full scale experiments were conducted under the dynamic tropical climate of Thailand. Annual simulations using full-year weather records were undertaken for a model room for cases of north and south facing windows to establish appropriate monthly slat adjustment angles that block undesired direct sunlight while guaranteeing the maximum possible view of exterior surroundings. Window luminance and work plane illuminance levels were examined and compared with proposed thresholds for comfortable working environments from previous studies. Lighting energy consumption and savings were also investigated in comparison to windows with heat reflective glass, commonly preferred by building designers. The study showed that it is possible to save 40% to 60% of energy consumed by electric lamps, avoid glare and achieve a comfortable workspace with a good view of exterior surroundings for most of the year by use of adjustable external horizontal shading slats.   Keywords: free view fraction, external horizontal slats, glare, energy savings.